2022
DOI: 10.3390/molecules27196239
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Triadica sebifera (L.) Small Extracts, Antifeedant Activities of Extracts, Fractions, Seed Oil and Isolated Compounds against Plutella xylostella (L.) and Their Effect on Detoxification Enzymes

Abstract: Plutella xylostella L. is one of the world’s major pests of cruciferous crops. The indiscriminate use of synthetic insecticides has led to insecticide resistance and resurgence, and has been harmful to non-target organisms and the environment. Botanical insecticides are the best alternatives to synthetic pesticides for the management of pests in organic agriculture and integrated management. T. sebifera is an invasive species and has good potential as an insecticide due to the availability of plant material in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Novel pesticides to control P. xylostella are urgently needed to combat these environmental safety challenges. Previous studies have shown that plant extracts and derived bioactive compounds have a variety of biological activities to control pests, and they provide an alternative to synthetic insecticides due to their biodegradable nature and safety for non-target organisms [7,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel pesticides to control P. xylostella are urgently needed to combat these environmental safety challenges. Previous studies have shown that plant extracts and derived bioactive compounds have a variety of biological activities to control pests, and they provide an alternative to synthetic insecticides due to their biodegradable nature and safety for non-target organisms [7,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Active compounds derived from plants or plant products have important bioactive functions and potential applications in agricultural pest management [4,27,31]. They often have a similar mode of action to synthetic insecticides [32], and may be able to provide precursor compounds for synthetic pesticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of all the problems involved in the adoption of this control method, it is necessary to search for more sustainable measures as an alternative way to contain the attack of agricultural pests. A trend that has shown promise and is gaining space in the field of research is the investigation of the activity of botanical extracts against plant parasites [81].…”
Section: Bio-molecules To Control Plant Pathogensmentioning
confidence: 99%
“…On this basis, the antifeedant effect of invasive plants can be tested by analyzing the damage pattern of native plants around invasive plants and then exploring the defense strategies of the invasive plants. Studies have documented antifeedant effects of invasive plants on herbivorous insects ( Liu et al., 2020b ; Dolma and Reddy, 2022 ). However, these studies mainly focused on the allelopathy of invasive plants and rarely involved the distribution patterns of native herbivorous insects that are impacted by invasive plants ( Liu et al., 2020b ).…”
Section: Introductionmentioning
confidence: 99%